Comparative proteomic analysis of plasma exosomes reveals the functional contribution of N-acetyl-alpha-glucosaminidase to Parkinson’s disease - Yuan Zhao; Yidan Zhang; Xin Liu; Jian Zhang; Ya Gao; Shuyue Li; Cui Chang; Xiang Liu; Guofeng Yang (Neural Regeneration Research)
Parkinson’s disease is the second most common progressive neurodegenerative disorder, and few reliable biomarkers are available to track disease progression. The proteins, DNA, mRNA, and lipids carried by exosomes reflect intracellular changes, and thus can serve as biomarkers for a variety of conditions. In this study, we investigated alterations in the protein content of plasma exosomes derived from patients with Parkinson’s disease and the potential therapeutic roles of these proteins in Parkinson’s disease. Using a tandem mass tag-based quantitative proteomics approach, we characterized the proteomes of plasma exosomes derived from individual patients, identified exosomal protein signatures specific to patients with Parkinson’s disease, and identified N-acetyl-alpha-glucosaminidase as a differentially expressed protein. N-acetyl-alpha-glucosaminidase expression levels in exosomes from the plasma of patients and healthy controls were validated by enzyme-linked immunosorbent assay and western blot. The results demonstrated that the exosomal N-acetyl-alpha-glucosaminidase concentration was not only lower in Parkinson’s disease, but also decreased with increasing Hoehn–Yahr stage, suggesting that N-acetyl-alpha-glucosaminidase could be used to rapidly evaluate Parkinson’s disease severity. Furthermore, western blot and immunohistochemistry analysis showed that N-acetyl-alpha-glucosaminidase levels were markedly reduced both in cells treated with 1-methyl-4-phenylpyridinium and cells overexpressing α-synuclein compared with control cells. Additionally, N-acetyl-alpha-glucosaminidase overexpression significantly increased cell viability and inhibited α-synuclein expression in 1-methyl-4-phenylpyridinium-treated cells. Taken together, our findings demonstrate for the first time that exosomal N-acetyl-alpha-glucosaminidase may serve as a biomarker for Parkinson’s disease diagnosis, and that N-acetyl-alpha-glucosaminidase may reduce α-synuclein expression and 1-methyl-4-phenylpyridinium-induced neurotoxicity, thus providing a new therapeutic target for Parkinson’s disease.